Los sistemas de gestión documental por resultados para mejorar la gestión de procesos de homologación en la facultad de Administración, Finanzas e Informática, durante el 2023 - Miranda Tobar, Carlos Víctor (2023)
The use of technology in educational processes has been vital in current times; document management systems have helped significantly to reduce process times that usually take longer than desired; the accreditation process in the Administrative Faculty of Finance and Computer Science usually takes considerable time to be carried out. Therefore, in the present work a document management system is designed to improve the homologation process in the Administrative Faculty of Finance and Informatics. For this purpose, an integral methodology was followed that included the programming of the system, through programming languages such as HTML, CSS, PHP, JavaScript and SQL, as well as detailed studies of technologies and costs, and the exhaustive analysis of materials related to document management systems and approval processes, due to the ease of integration to the Technical University of Babahoyo, this can be added to the systems of the same, without major mishap. Essentially, the adoption of a results-oriented document management system was shown to be an effective solution to improve the homologation processes in the Faculty of Finance and Informatics of the Technical University of Babahoyo, achieving significant optimization and contributing to the overall efficiency of the institution.